2023
DOI: 10.3389/fonc.2023.1047388
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in PSA levels predict prognostic outcomes in prostate cancer patients undergoing androgen -deprivation therapy: A multicenter retrospective analysis

Abstract: BackgroundAndrogen-deprivation therapy (ADT) is used for the treatment of prostate cancer. However, the specific risk factors for the development of castration-resistant disease are still unclear. The present study sought to identify predictors of patient prognostic outcomes through analyses of clinical findings in large numbers of prostate cancer patients following ADT treatment.MethodsData pertaining to 163 prostate cancer patients treated at the Second Affiliated Hospital of Bengbu Medical University and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The study revealed that both nPSA and TTN were significant prognostic factors for the progression to CRPC in patients with mHSPC. Furthermore, patients with nPSA levels of ≤ 0.2 ng/ml and TTN ≥ 9 months significantly delayed disease progression and prolonged OS (29,30). However, there is no conclusive evidence to determine whether these two measures significantly improve or worsen patient outcomes, and their specific impact on patient prognosis remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that both nPSA and TTN were significant prognostic factors for the progression to CRPC in patients with mHSPC. Furthermore, patients with nPSA levels of ≤ 0.2 ng/ml and TTN ≥ 9 months significantly delayed disease progression and prolonged OS (29,30). However, there is no conclusive evidence to determine whether these two measures significantly improve or worsen patient outcomes, and their specific impact on patient prognosis remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…False positive results of PSA screening, and prostatic puncture will cause overexamination and over-treatment, which undoubtedly increases the psychological pressure and medical expenses for the patients [19]. When the PSA levels exceeds 4.0 ng • ml -1 or DRE result is abnormal, it usually suggestive of Pca, but the standards may change along with the changes in age, race and personal physiological conditions [20]. PSA detection is unable to distinguish between BPH or Pca.…”
Section: Diagnostic Methods Currently Used In Prostate Cancermentioning
confidence: 99%
“…However, the tumors in some ADT-treated patients eventually progressed to a more aggressive form, called castration-resistant PCa (CRPC). CRPC exhibits a significant increase in prostate-specific antigen (PSA) value and/or radiographic progression despite castration [3,4]. Currently, the approved therapies for CRPC include chemotherapy, immunotherapy, radiation therapy, targeted therapies and hormone therapies (i.e., by AR inhibitors) [5].…”
Section: Introductionmentioning
confidence: 99%